Pengaruh Media Sosial Instagram terhadap Perilaku Menyimpang Mahasiswa Universitas Mercu Buana Yogyakarta Kampus 3 - Ridho AlFattah (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
This study aims to investigate the impact of Instagram social media use on deviant behavior among students at Campus 3 of Mercu Buana University in Yogyakarta. The phenomenon of increased intensity of social media use among students is the main basis of this study, in which Instagram not only functions as an instrument of communication and self-expression, but also as a medium that has the potential to trigger various forms of deviant behavior, such as cyberbullying, self-image manipulation, and social norm violations. The research method used integrates quantitative methods with descriptive design and simple linear regression analysis. Data was collected through a survey distributed to 100 active student participants, whose sample was determined using a simple random sampling method. Validity and reliability tests showed that all research instruments met the criteria for validity and reliability, as reflected in a Cronbach's Alpha value of 0.946. The relationship between Instagram and deviant behavior among students is represented by the regression equation Y = 2.300X + 0.641. These findings indicate that an increase in the frequency of Instagram use correlates with an increase in the potential for students to adopt deviant behavior. It is hoped that this study can serve as a basis for improving digital literacy and educating students on the ethical use of social media in a university environment.